2008
DOI: 10.1002/sia.2722
|View full text |Cite
|
Sign up to set email alerts
|

ToF‐SIMS study of 1‐dodecanethiol adsorption on Au, Ag, Cu and Pt surfaces

Abstract: Time-of-flight secondary ion mass spectrometry (ToF-SIMS) has been used to perform a chemical analysis of long-chain thiol (CH 3 (CH 2 ) 11 SH)-treated gold, silver, copper and platinum surfaces. All the mass peaks from positive and negative ion spectra within the range m/z = 0-2000 u are studied. ToF-SIMS data revealed that on gold, silver and copper substrates 1-dodecanethiol form dense standing-up phases, but on platinum being a catalytically active substrate, we were able to identify also surface-aligned p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…During the extraction, the temperature of the solution was kept at 50 C and the sample was stirred with a constant stirring rate (300 rpm). Different extraction times were applied for each fiber (10,20,30,40,60, and 90 min) to find out the optimum extraction time, where equilibrium was reached. After extraction, the analytes were thermally desorbed for a period of 5 min (to avoid carryover effects) at different desorption temperatures (100 C, 150 C, 200 C, and 250 C) in the injector of the gas chromatograph to investigate the effect of desorption temperature.…”
Section: Spme Fibers With Alkanethiolsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the extraction, the temperature of the solution was kept at 50 C and the sample was stirred with a constant stirring rate (300 rpm). Different extraction times were applied for each fiber (10,20,30,40,60, and 90 min) to find out the optimum extraction time, where equilibrium was reached. After extraction, the analytes were thermally desorbed for a period of 5 min (to avoid carryover effects) at different desorption temperatures (100 C, 150 C, 200 C, and 250 C) in the injector of the gas chromatograph to investigate the effect of desorption temperature.…”
Section: Spme Fibers With Alkanethiolsmentioning
confidence: 99%
“…The equilibration time is defined as the time after which the amount of the extracted compound remains constant. For this purpose, different extraction time intervals (10,20,30,40,60, and 90 min) were applied. DVB-Carboxen-PDMS and Carboxen-PDMS SPME fibers showed an increase of the detector response (peak area) for most detected compounds, thereby increasing the extraction time (Table 1).…”
Section: Extraction Timementioning
confidence: 99%
See 1 more Smart Citation
“…applications, several research works have dealt with the study of the thiol SAMs' structure [14][15][16][17][18][19][20][21][22][23][24][25] or with the development of new techniques aimed at creating patterned surfaces [26][27][28]. It has been found that desorption studies are very useful in the study of the SAMs' structure [29,30].…”
mentioning
confidence: 99%
“…This chapter explains how bond enhancement varies according to the structural integrity (thermal and mechanical) of the monolayer coating which is a function of the thickness of the monolayer. Gathered with the findings, we have evaluated on the bonding mechanism between two metallic surfaces and coated surfaces in Chapters 3 and 4, a working hypothesis is derived which highlights three key factors enabling low temperature direct metal thermocompression bonding, namely: (1) surface passivation,(2) thermal activation through bond-weakening or desorption of SAMs and(3)mechanical displacement of the weakened SAMs layer.Self-assembled monolayers on planar substrates such as thin metallic films on silicon wafers, mica or glass are most commonly characterized due to the ease of preparation as well as its compatibility with several surface analytical techniques such as X-ray photoelectron spectroscopy (XPS)[76,90,91] , contact angle measurements[76,92], surface plasmon resonance spectroscopy (SPRS)[93], time-offlight secondary ions mass spectroscopy (TOF-SIMS)[84,94,95]and many more. This chapter presents several surface studies to evaluate the passivating properties of alkanethiols at various chain length on gold metal by comparing the amount of carbon…”
mentioning
confidence: 99%